2016
DOI: 10.1080/1744666x.2016.1188006
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options for cutaneous lupus erythematosus: recent advances and future prospects

Abstract: Introduction Treatment and prevention are of critical importance in patients with cutaneous lupus erythematosus (CLE), as the disease can have a devastating effect on patient well-being and quality of life. Areas Covered We conducted a selective search of the PubMed database for articles published between December 2010 and November 2015. This review encompasses both non-pharmaceutical (photoprotection, smoking cessation, drug withdrawal, and vitamin D replacement) and pharmaceutical (topicals, antimalarials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 127 publications
(129 reference statements)
0
10
0
4
Order By: Relevance
“…Despite their similarities in efficacy, 35 HCQ is generally the first systemic agent to be prescribed, in part because of the greater risk of toxic retinopathy with CQ. 36 A recent double-blinded randomized controlled parallel-group trial showed greater improvements in the investigator's global assessment in the HCQ group compared to placebo (51.4% versus 8.7%). 37 In those patients who fail to improve with HCQ alone, the addition of quinacrine increases the likelihood of response.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…Despite their similarities in efficacy, 35 HCQ is generally the first systemic agent to be prescribed, in part because of the greater risk of toxic retinopathy with CQ. 36 A recent double-blinded randomized controlled parallel-group trial showed greater improvements in the investigator's global assessment in the HCQ group compared to placebo (51.4% versus 8.7%). 37 In those patients who fail to improve with HCQ alone, the addition of quinacrine increases the likelihood of response.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…105 HCQ is superior to CQ with its greater risk of toxic retinopathy. 106 HCQ is the preferred agent because of its efficacy and tolerability. 4,107 Considering the safety, HCQ can be also prescribed to pregnant women.…”
Section: Established Therapiesmentioning
confidence: 99%
“…Intralesional steroid injections can be used for localized disease, particularly the DLE subtype (Chang and Werth, 2016). Intramuscular corticosteroid injections can also be used.…”
Section: Treatment Optionsmentioning
confidence: 99%